Proficiency Level in English Writing of the Students Enrolled at Isabela State University San Mariano Campus - Galiza, Clarinda C. (International Journal of Psychosocial Rehabilitation, 2020)
The study focused on identifying the English Writing Proficiency of students at Isabela State University San Mariano campus. The descriptive survey method was utilized involving 632 students. The English Writing Proficiency was identified by asking the students to write a composition under controlled condition. The outputs of the students were evaluated using a rubric covering organization, mechanics, content and grammar. Majority of the students were found out to have committed errors on writing incomplete sentences, spelling, tenses of verbs and on subject and verb agreement. Furthermore, the English Writing Proficiency of students is dependent on their age, sex, curriculum level, parents’ educational attainment and dialect spoken. It is recommended that professors, instructors, teachers of English must expose students in writing exercises like writing essays, short stories, poems, editorial, news articles, etc. for the enhancement of their proficiency in writing. Finally, teachers must teach the students the principles of clear and effective writing like correct spelling, correct use of punctuations, grammar, diction and among others.